Scenario Planning For Ceramic Tile Manufacturing Company PT ABC - Dhiannova, Charlie; Djunita Pasaribu, Rina (Publisher Cv. Inara, 2025)
Every Company requires a strategy to develop in the long term, upholding its position in the market with increasing sales volume, and profitability that ensures the sustainability of the Company itself. Mapping the path for the Company's future is a challenge in the strategy formulation, specifically in the face of disruptions which often occur both internally and externally. PT ABC's strategy must consider or prepare for all reasonable future possibilities to maintain the continuity of its business. The scenario planning approach prepared as part of PT ABC's strategy formulation will minimize the strategy implementation failure risk and provide a comprehensive picture of when to replace, change, or adjust the strategy through the early warning system, which monitors the company's external environment. The purpose of this study is to formulate a scenario planning by analyzing and investigating the driving forces, the critical uncertainties that arise and influence PT ABC's ceramic tile business, along with devising early warning signals in order that PT ABC becomes able to determine which possible scenarios to use and what actions must be taken to deal with those scenarios. This study uses qualitative research methodology using primary and secondary data to determine the driving forces that will affect PT ABC's ceramic tile business until 2030. The obtained data is analyzed using the scenario planning approach, PESTEL analysis, and Porter's Five Forces analysis (Industry analysis) to create a scenario matrix that reflects critical uncertainties that will influence PT ABC's business in the future. The scenarios indicate possible future situations and offer strategic options for the company to manage the implications of each scenario. Before a scenario occurs, the company must determine the early warning signal to alert the company to which scenario will occur and what action should be taken. By establishing a comprehensive scenario planning, the company can develop strategies that can help it confidently envision its future business.